Kajian Tax Planning PPH 21 tentang Tarif Pemotong Pajak Penghasilan Pasal 21 atas Penghasilan Sehubungan dengan Pekerjaan, Jasa atau Kegiatan Wajib Pajak Orang Pribadi - Nurhidayah, Dhea Alifia; Setiawan, uhammad Surya; Noura, Ghaniya; Wahono, Puji; Pahala, Indra (BUDGETING : Journal of Business, Management and Accounting, 2024)
The aim of this research is to examine the impact of changes in the taxation regulations for Income Tax Article 21 (PPh Article 21), since the enactment of PP 58 of 2023 as a replacement for the Director General of Taxation Regulation no. PER/16/PJ/2016. The method used in this research is a type of quantitative descriptive research using a comparative study approach. The variable studied is tax planning as variable X, while variable Y is income tax. The data collection technique in this research is document review, namely reviewing financial reports from the Independent Education Accreditation Institute (LAMDIK). Data analysis and processing The technique used is calculating the amount of PPh Article 21 for employees through tax planning for PPh Article 21 using the Director General of Taxes Regulation PER/16/PJ/2026 and PP 58 of 2023 approach. By implementing the calculation of PPh Article 21 using PP 58, it was found easier and simpler because there is no need to consider income that must be annualized as per the calculation method using Regulation of the Director General of Taxes PER No.16/PJ/2016. Furthermore, from the perspective of income tax planning, it is easier to do because the tax rate (TER) as determined by PP 58 of 2023 is a tax rate using the single rate method. Keywords: , Income Tax Management, Tax Planning Income Tax Article 21.